Evaluation of exercise capacity using two field tests in patients with metabolic syndrome. Issue 7 (27th March 2021) - Bozdemir Ozel, Cemile; Arikan, Hulya; Demirtas, Raziye Nesrin; Saglam, Melda; Calik-Kutukcu, Ebru; Vardar-Yagli, Naciye; Inal-Ince, Deniz; Akalin, Aysen; Celer, Ozgen; Sonbahar-Ulu, Hazal; Cakmak, Aslihan
Abstract: Purpose: Field tests are popular for assessing exercise capacity because they are practical and have established validity. The objective of this study was to compare physiological responses and exercise performance of patients with metabolic syndrome in two field tests of exercise capacity. Material and Methods: Forty-seven patients diagnosed with metabolic syndrome participated in this cross-sectional study. Exercise capacity was assessed using incremental shuttle walk test and six-minute walk test. Factors determining exercise capacity and agreement between the two tests were also investigated. Results: Metabolic syndrome patients achieved a significantly greater percentage of predicted maximal heart rate, blood pressure, and longer distance in the incremental shuttle walk test than in the six-minute walk test ( p < 0.001). Gender and body mass index explained 48.5% of the variance in six-minute walk test distance ( R = 0.697, R 2 = 0.485, F (2-46) = 20.737, p < 0.001). Body mass index and fat-free mass explained 55% of the variance in incremental shuttle walk test distance ( R = 0.746, R 2 = 0.557, F (2-46) = 27.623, p < 0.001). Conclusions: Despite the agreement in the percentages of predicted maximal heart rate during these two field tests, the incremental shuttle walk test may be a better assessment tool than the six-minute walk test because it elicits more pronounced and definitive physiological responses to exercise tolerance in patients with metabolic syndrome. IMPLICATIONS FOR REHABILITATION: The incremental shuttle walk test can be used to evaluate exercise capacity in metabolic syndrome. The incremental shuttle walk test elicits greater physiological responses than the six-minute walk test. The incremental shuttle walk test may be preferable over the six-minute walk test in investigating exercise capacity. Both tests can guide and assist in the evaluation of this patient population in clinical practice. Body mass index affected distance in both exercise tests.